2019
DOI: 10.1016/j.bpj.2019.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Disulfide Chaperone Knockouts Enable In Vivo Double Spin Labeling of an Outer Membrane Transporter

Abstract: Recent advances in the application of electron paramagnetic resonance spectroscopy have demonstrated that it is possible to obtain structural information on bacterial outer membrane (OM) proteins in intact cells from extracellularly labeled cysteines. However, in the Escherichia coli OM B 12 transport protein, BtuB, the double labeling of many cysteine pairs is not possible in a wild-type K12-derived E. coli strain. It has also not yet been possible to selectively label single or paired cysteines that face the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(51 citation statements)
references
References 34 publications
1
50
0
Order By: Relevance
“…1a). These included multiple sites on the extracellular loops of BtuB (18)(19)(20) as well as two sites in the core region (18).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…1a). These included multiple sites on the extracellular loops of BtuB (18)(19)(20) as well as two sites in the core region (18).…”
Section: Resultsmentioning
confidence: 99%
“…Recent work has also shown that the efficient incorporation of pairs of spin labels to make distance measurements using DEER required the use of a strain deficient in the disulfide bond formation (Dsb) chaperone system (18). We tested several additional single cysteine mutants in BtuB using a DsbA - strain to determine whether spin labeling of additional sites in the core was possible.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations